Edukasi Hukum Pengelolaan Kawasan Perairan Secara Berkelanjutan - Abunawas Abunawas (Indonesian Journal Publisher, 2024)
Legal education regarding sustainable water area management for teenagers or school-aged children is a strategic effort to form a generation that is environmentally aware and responsible. The aim of community service activities (PKM) for legal education on sustainable management of marine areas is to socialize and educate teenagers about the importance of awareness of the rules governing the sustainable use of marine resources. With a deep understanding of environmental law, children can develop an ethical character and be sensitive to ecological issues, and avoid unlawful behavior. The partners for this activity are students from SMPN 8 Kubu Raya which is located in the coastal area of ​​Sungai Kakap Kubu Raya District. The activity was attended by 30 students, carried out using lecture and scientific discussion methods. Based on the evaluation of activities carried out at the beginning and end of the activity by giving questionnaires to participants, it showed an increase in the percentage of participants in understanding the training material provided.